Polystichum clarinervium (subg. Haplopolystichum; Dryopteridaceae), a new fern from Emei shan, China - Li, Chun-Xiang; Patel, Nikisha R.; Zhang, Li-Bing (Phytotaxa, 2016)
A new fern species, Polystichum clarinervium, a member of P. subg. Haplopolystichum (Dryopteridaceae), is described and illustrated from Emei shan, Sichuan Province, Southwest China. The new species is similar to P. deltodon, but the former has pinnae slightly imbricate, pinna apex rounded, and veins clear, while the latter has pinnae not imbricate, pinna apex acute, and veins obscured. Polystichum clarinervium was found on a limestone slope under sparse forest at an elevation of 1300 m and is currently known from two small populations. It is classified as Critically Endangered (CR) following IUCN Red List criteria.